Biochemical and Microbiological Quality of Formic Acid Silage and Lactobacillus Fermented Silage - B., Madhusoodana Rao; U.S., Jayaprakash Babu; D., Imam Khasim; K.G., Ramachandran Nair (Fishery Technology, 2025)
Acid silages (AS) were prepared by mixing formic acid with silver belly (Leiognathus sp.) mince at 2%, 2.5% and 3% (v/w) and fermented silages (FS) were prepared by mixing Lactobacillus plantarum culture with fish mince at 5% (v/w) and molasses at 10% and 12% (v/w). Sodium benzoate was added at 0.5% (w/w) level to FS to inhibit mould growth. pH of 2.5%AS and 3%AS fell below 4.5 within 2 days and stabilized at 4.24 and 4.01, respectively. pH of 2%AS reached a minimum value of 4.68. In 10%FS and 12%FS, the pH dropped to less than 4.5 by the end of 1st day indicating good lactic acid fermentation by Lactobacillus plantarum. Crude protein of the silages ranged between 18.22% and 19.17%. Fat was lower in FS .(1.0 - 1.14%) than in AS (3.67 - 5.13%) on wet basis. NPN of FS was found to be lower than that in AS which indicates lesser protein breakdown, a-amino nitrogen in FS changed to 21% of TN in 10% FS and 12%FS from an initial concentration of 11% of TN, which was lower than that in AS. PV was lower in AS than in FS. Microbiological quality of AS and FS was found to be good as indicated by the absence of total coliforms, faecal coliforms, E. coli. Salmonella, Vibrio cholerae, coagulase positive Staphylococci and H2S producing bacteria. Total yeast mould count was highest in 2% AS (1600/g).